2010
DOI: 10.1007/s11104-009-0263-z
|View full text |Cite
|
Sign up to set email alerts
|

Improving fertility and productivity of a highly-weathered upland soil in subtropical China by incorporating rice straw

Abstract: The transfer of rice straw from paddy fields to upland areas was proposed in our study as an innovative practice to improve the fertility of the highly-weathered and poor upland soils, as well as to mitigate environmental impacts from rice production system (e.g., the large application of chemical fertilizers, straw burning, CH 4 emission from decomposed straw) in the subtropical China. Data from an 8-year field experiment with sweet potato and rapeseed show that, the contents of organic matter and total nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 39 publications
4
58
1
1
Order By: Relevance
“…In our study, the crop biomass and grain yields were higher with straw incorporation than conventional tillage (NA). Similar effects were reported by Zhu et al (2010) based on an 8-year field experiment in China. Note: RP, before treatment; NA, no straw incorporation; LA, incorporation of straw at a low rate of 4.5 Mg ha À1 yr À1 maize straw; MA, incorporation of straw at a medium rate of 9.0 Mg ha À1 yr À1 maize straw; HA, incorporation of straw at a high rate of 13.5 Mg ha À1 yr À1 maize straw.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the crop biomass and grain yields were higher with straw incorporation than conventional tillage (NA). Similar effects were reported by Zhu et al (2010) based on an 8-year field experiment in China. Note: RP, before treatment; NA, no straw incorporation; LA, incorporation of straw at a low rate of 4.5 Mg ha À1 yr À1 maize straw; MA, incorporation of straw at a medium rate of 9.0 Mg ha À1 yr À1 maize straw; HA, incorporation of straw at a high rate of 13.5 Mg ha À1 yr À1 maize straw.…”
Section: Discussionsupporting
confidence: 87%
“…No significant difference in soil P accumulation was observed when compared between straw and MF treatments, probably because P content in straw was relatively lower compared with the P in manure. Zhu et al (2010) also reported that, in an 8-year field experiment, chemical fertilizers plus straw incorporation did not significantly increase soil TP and Olsen-P contents in subtropical region of China compared with chemical fertilizer application. Phosphorus accumulation in soil under a certain fertilization treatment or P budget usually exhibited a linear correlation with management history (Whalen and Chang 2001;Messiga et al 2010;Ciampitti et al 2011).…”
Section: Effects Of Organic Amendments On Soil P Accumulationmentioning
confidence: 92%
“…Organic amendments, such as application of manure and compost, and the incorporation of crop residues are effective methods to improve soil fertility and productivity (Zhu et al 2010). Recently, the incorporation of crop residues to the soil is highly advocated in China, since the burning of residues in situ by farmers, as usually did, is causing a serious waste of nutrient resources besides contributing to air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium (Cd) is one of heavy metal that is not biodegradable and considered to be a very hazardous element to environment [2]. Mulching with plant straw on soil surface is one of the natural methods using in agricultural production, and straw mulch decomposes in the soil and converts into organic matter, allelopathic substances and other nutrients, which can fertilize the soil, improve soil texture and affect physiological and biochemical activities of soil microorganisms [3][4]. If we apply the plant straw in heavy metal contaminated soil, the plant straw could affect the heavy metal bioavailability, and decrease or increase the heavy metal absorption of living plant [5].…”
Section: Introductionmentioning
confidence: 99%